Training of employees directly in the organization (the employer) and the possibility of reimbursement by the employer of the costs incurred (Journal of actual problems of jurisprudence, 2018)
The issues of ensuring professional qualification, with observing the principles of conscientiousness and integrity of subjects of labor relations are of paramount importance in the personnel policy of state bodies and non-governmental organizations. The obviousness of the need to improve the range of legal and organizational measures is beyond doubt. The article deals with problems related to the training, retraining and advanced training of employees directly in the organization (the employer). Regulatory legal acts that regulate these legal relations were analyzed and summarized. The official position of the authorized state bodies is presented. The main problems encountered by employers are considered. On the basis of the legal analysis, practical recommendations are given on the organization of training directly within the organization (the employer) within the framework of the current legislation of the Republic of Kazakhstan, as well as proposals on amending some legislative acts to improve norm-setting activities. The aim of the study is also a comprehensive review of the learning process, with the possibilityof highlighting the optional but extremely important tasks facing educational activities. practicalapplication of the legal mechanism discussed in this article will allow reconsidering the content of theeducational process that arises between the employer, as a mentor, and the employee as a student.Key words: vocational training, retraining and advanced training of employees directly in the organization(the employer), conclusion of a training contract, withholding from wages, reimbursement ofemployer costs associated with training an employee.